MEMBUMIKAN SEJARAH SOSIAL - Johan Robert Saimima (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2014)
This article attempts to discuss about social history as an important part of the new Indonesianhistoriography. Through writing this article a perspective of social history is described to provideknowledge and a critique of political history which is so famous, as well as introducing the writing ofsocial history as a comprehensive history.Author discusses social history with political history in the rapidly growing Indonesianhistoriography, then as a critique of the political history that laudes great people, displayed socialhistory as history that takes sides to the populist or marginal in the society. Social history is veryrelevant to be developed more widely in Indonesia, because the context of Indonesian society arethose who are most marginalized people, such as: farmers, fishermen, laborers, the homeless, etc.In order to develop a social history, the interdisciplinary approach can be used in writing.With this process, the social science concepts can be used to strengthen the explanation andinterpretation